Growth of white shrimp (Litopenaeus vannamei) and environmental variation in greenhouse ponds located in Zhoushan City of Zhejiang Province - LU Lingzi; LI Yunmeng; WANG Yan (浙江大学学报. 农业与生命科学版)
In order to optimize prawn breeding mode, growth of white shrimp (Litopenaeus vannamei), phytoplankton species and environmental variation in six greenhouse ponds located in Zhoushan City of Zhejiang Province were monitored at the interval of 15 d between August 16 and October 30, 2017. The results showed that the body length (L/cm) and body mass (m/g) of the white shrimp increased with the breeding time (t/d), and the regression equations were described as L=0.744 9×t 0.594 6 and m=0.004 2×t 1.823 7, respectively. During the investigation period, water temperature and pH in the ponds decreased with the prolongation of time. The reactive phosphate (<alternatives>PO43－<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/253A191F-784D-4abd-8D8D-1C852615DD1D-M001.jpg"/></alternatives>-P) and total phosphorus (TP) contents in the ponds significantly increased after the 15th day of stocking the shrimp seed. The total ammonia nitrogen (TAN), total nitrogen (TN) contents and five-day biochemical oxygen demand (BOD5) value significantly increased, while the total alkalinity (TA) significantly decreased, after the 30th day of stocking the shrimp seed. The chemical oxygen demand (CODMn) value significantly increased, while the dissolved oxygen (DO) value declined, after the 45th day of stocking the shrimp seed. The species of Chlorophyta, Cyanophyta, Bacillariophyta and Euglenophyta dominated in the ponds. Chlorophyll a (Chl a) content increased from the 0th to the 30th day after stocking the shrimp seed and then gradually declined. Growth rate in body length or body mass of the shrimp positively correlated to nitrite nitrogen (<alternatives>NO2－<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/253A191F-784D-4abd-8D8D-1C852615DD1D-M002.jpg"/></alternatives>-N), nitrate nitrogen (<alternatives>NO3－<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/253A191F-784D-4abd-8D8D-1C852615DD1D-M003.jpg"/></alternatives>-N), TN, <alternatives>PO43－<inline-graphic xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="graphic/253A191F-784D-4abd-8D8D-1C852615DD1D-M004.jpg"/></alternatives>-P, TP, Chl a contents, and CODMn, BOD5 values, but negatively correlated to water temperature, DO value, pH and TA. These results suggest that water temperature, DO, pH and TA might be the environmental factors regulating growth of the white shrimp reared in the greenhouse ponds. Abnormally high water temperature in summer might limit growth of the white shrimp, and maintaining pH constant should be an important aspect in water quality management.